Pacification, Capital Accumulation, and Resistance in Settler Colonial Cities: The Cases of Jerusalem and Rio de Janeiro - Huberman, Bruno [UNESP] (2019)
Approaching urban social conflicts in Brazil and in Palestine/Israel in terms of settler colonial theory allows the identification of the historical racist structures involved in the violent pacification of racialized native populations. Settler colonialism does not end with the declaration of independence but persists in the postcolonial context through the constant expropriation, extermination, confinement, and assimilation of racialized populations in the service of capitalist accumulation by settler elites. The cases of Jerusalem and Rio de Janeiro exemplify this process.